P190 The impact of endoscopist performance on distal adenoma detection and colorectal cancer incidence. (19th June 2022) - Power, Sharon; Wooldrage, Kate; Cross, Amanda
Abstract : Introduction: A high-quality endoscopic examination is key for the detection and removal of adenomas, precursor lesions to colorectal cancer (CRC). Adenoma detection rates (ADRs) are frequently used to measure endoscopist performance but improving other components of the examination could improve adenoma detection. The aim of this study is to investigate how endoscopist performance at flexible sigmoidoscopy (FS) screening affects distal adenoma detection and long-term distal CRC incidence. Methods: Among 34, 139 participants who received FS screening by the main endoscopist at one of 13 centres in the UK FS Screening Trial, median follow-up was 17 years. Factors examined included bowel preparation quality, insertion and withdrawal time, segment of bowel reached, family history of CRC, patient pain and ADR. Odds ratios (OR) and 95% confidence intervals (CI) for distal adenoma detection were calculated by logistic regression. Cox regression was used to estimate hazard ratios (HR) for distal CRC incidence. Results: The overall ADR was 12% and 168 distal CRCs were diagnosed. In multivariable models, a family history of CRC (yes vs. no, OR 1.41, 95%CI 1.22-1.63), poor bowel preparation quality (OR 2.86, 95%CI 1.25-6.55) and higher insertion and withdrawal times (≥4.00 vs. <1 minute: OR 1.93, 95%CI 1.44-2.58; OR 45.65, 95%CI 35.20-59.21, respectively) were associated with distal adenoma detection. In addition to longer insertion and withdrawal times, being screened by an endoscopist with a low ADR, compared to a high ADR, was positively associated with distal CRC incidence (HR 4.71, 95%CI 2.65-8.38). Conclusions: These findings highlight the importance of key aspects of endoscopic examinations that are vital to improve distal adenoma detection.